Personal finance app - Ng, Jonathan Yu Kiat (Nanyang Technological University, 2023)
Personal finance management is an important part of life as it helps with financial literacy and planning. Being able to plan your budget is one of the most basic yet most effective way to manage our income. However, many do not actually track their expenses due to them not knowing how to do it. This mobile application is very simple to use and would help non-tech-savvy individuals be able to track their finance easily. This application would allow individuals to be able to see their finance and plan for their expenses.